Subprodutos da uva para utilização em dietas de frango de corte - Rotava, Rui (2007)
The aim of this experiment was to determine in vitro the composition, the antibacterial, antioxidant and tanning activity of grape by-products (Vitis vinifera) for its exploitation in the poultry industry. The crude fiber content of the pomace of 31, 6% and for lignin of the seeds it was 61,2%. The pressed seeds contained 13,4% of crude oil, whose composition of fat acid has 67,73% of linoleic acid. To be studied as growth promoter of birds, polar compound had been extracted from the defatted grape seed in a solution with acetone: water: acid ascetic, resulting in 10,3% of extract from the defatted grape seed extract (ESUD) that, when analyzed, evidenced the presence of anthocyanic pigments and condensed tannins. The ESUD presented high antibacterial activity against strains of S. aureus and E. coli, but not against Salmonella sp. The antioxidant activity of the ESUD presented a percentage of inhibition of 1,1-difenil-2-picrilhidrazila comparable to the ascorbic acid, whose effect reached its maximum at 200 μg/ml. The capacity of tannins to bind protein was considered low for the seed and SUD and high for the ESUD. Later on, the inclusion effect of the grape seed and by-product as additives in the diets of poultry upon growth performance had been evaluated for apparent digestibilidade of the dry matter (CDMS), organic matter (CDMO) and crude protein (CDPB), blood levels of cholesterol, triglycerides, total proteins and glucose, beyond cecal pH. Six hundred day old Ross chicks were distributed in completely randomized design, from 1 to 21 days of age, with six treatments, five repetitions of 10 birds, inoculated or not with strains of E. coli, constituting a 6x2 factorial. Initial feed was used constituting the following treatments: T1-negative control; T2-positive control-0.05% of flavomycin and colistin sulphate; T3-0,04% extract of ESUD; T4-0,1% of grape seed (SUI); T5-0,47% of SUI and T6-2,35% of SUI. The inclusion of grape by-products did not influence the rates growth parameters, apparent digestibilidade or cholesterol levels but decrease levels of blood triglycerides. The inoculation decreased body weight, the weight gain, decreased the levels of blood total protein, and increased triglycerides and glucose and when associated with the ESUD, improved the CDMO. The contradictory results indicate the need for further experiments.